Relevance of virtual education in reading and writing. A systemic review - Céspedes Chauca, Milagros de Jesús (2022)
The present and future education demands new knowledge and methodologies to ensure that our children learn to read and write properly, even more so during the state of the pandemic, virtual education takes on a relevant place since it is the only way to connect with the students, but at the same time its effectiveness could be uncertain. The article is based on the systemic review that aims to analyze during the years 2017 to 2022, the relevant aspects during the learning of reading and writing in virtual education, using the prism statement as a methodology, the criteria of inclusion and exclusion, using as database: Scopus, Scielo and academic Google and EBSCO. The review answers the questions: Which countries have carried out research regarding virtual education and literacy? How many investigations have been carried out per year on the subject? What relevant aspects are considered in virtual education to teach reading and writing?; Having as a result of the analysis that the most carried out investigations are in the countries of Spain and the United States, evidencing in 2021 a considerable increase in investigations on the subject and that the responsibility of parents in this new learning modality is the backbone so that children can consolidate literacy, the potential value of the virtual educational program and the correct use of ICT in this type of study.